Akuntabilitas Keuangan dan Kontribusi Sosial Ritel Modern Terhadap Ekonomi Lokal: Kajian Akuntansi Organisasi Laba di Boalemo - Sukrianto; S. Lakoro, Fibriyanti (STIA Bengkulu, 2026)
This study aims to analyze the influence of financial accountability and the social contribution of modern retail on the local economy of Boalemo Regency. The rapid growth of modern retail, on the one hand, provides easier access to goods and creates employment opportunities, but on the other hand, it exerts pressure on the sustainability of micro, small, and medium enterprises (MSMEs) and traditional markets. This research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 30 modern retail outlets that have been operating for at least two years in Boalemo Regency, complemented by limited interviews and documentation. Data analysis was conducted using multiple linear regression with classical assumption tests. The results indicate that financial accountability has a positive and significant effect on the local economy, with a coefficient of 0.463 and a significance value of 0.003. The social contribution of modern retail also has a positive and significant effect on the local economy, with a coefficient of 0.298 and a significance value of 0.022. Simultaneously, financial accountability and social contribution have a significant effect on the local economy, with an Adjusted R² value of 0.64. These findings suggest that financial transparency, compliance with accounting standards, and the social contribution of modern retail play an important role in supporting regional economic stability, although the involvement of local MSMEs in the modern retail supply chain remains relatively limited. This study recommends strengthening local government regulations and integrating modern retail corporate social responsibility programs that are oriented toward strengthening the local economy and ensuring the sustainability of MSMEs.